The assessment of aristida adscensionis and rumex hypogaeus comparative and combine antioxidant potential - Dr Fahim Ullah Khan; Niazi, Maria; Surayia Shahab Rani; Khadija Khattak; Khalid Wahab; Zia UD Din; Osama Alam; Autif Hussain Mangi; Muhammad Reyan; Tariq Rahim; Zakim Ullah; Israr Ahmad (LIAQUAT MEDICAL RESEARCH JOURNAL, 2024)
Exogenous substances and cellular metabolism both produce free radicals in cells. The produced free radicals react with cell biomolecules, including DNA. The ensuing destruction of DNA, also known as oxidative DNA damage, which is connected to aging, carcinogenesis, and mutagenesis. The Aristida adscensionis plays an essential role in the modulation of free radicals. We examined the antioxidant therapy of individual or combined forms of the Aristida adscensionis and Rumex hypogaeus plant extracts. We noticed that Aristida adscensionis showed scavenging activity at various concentrations i.e. 50, 100, 250, 500, and 1000 ?g/ml was 42%, 50%, 62%, 69% and 75% respectively. The scavenging activity of Rumex hypogaeus at various concentrations was 43%, 52%, 58%, 66% and 75% against the standard of ascorbic acid. We noticed that the combined mixture of both plant extracts elucidated a significant antioxidant potential at different concentrations of 100 ?g/ml, 500 ?g/ml, and 1000 ?g/ml which were 58%, 70%, 74%, 81% and 86 %. Our research study demonstrates that combinaion of both plants’ extract mixtures had a more substantial antioxidant capacity than each extract individually. This property of these plants can be used for cancer treatment, however further robust data is required.